2022
DOI: 10.3390/ijerph19159310
|View full text |Cite
|
Sign up to set email alerts
|

Research on Spatial Differences and Driving Effects of Ecological Well-Being Performance in China

Abstract: The essential requirement of sustainable development is to maximize economic prosperity and well-being while remaining within natural boundaries. This study focused on three aspects. First, a unique ecological well-being performance (EWP) evaluation model was developed by combining subjective and objective well-being indicators to assess China’s EWP from 2006 to 2018. Second, the evolution of spatial differences in China’s EWP was examined using the Dagum Gini coefficient and four spatial polarization indicato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The reason, on the one hand, is that this study included non-natural resource inputs in the indicator system and the other is that the technological and economic development level of the Poyang Lake area was relatively backward, which leads to low eco-economic efficiency. Like most cities, EWP in the Poyang Lake area is constrained by eco-economic efficiency, suggesting that China still needs to promote the green economic transformation to improve human well-being sustainably [ 12 ]. In addition, the measurement results of this study showed that using a two-stage Super-NSBM model is more accurate and reasonable than using the Super-SBM model, which considers undesired outputs from a single-stage perspective.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reason, on the one hand, is that this study included non-natural resource inputs in the indicator system and the other is that the technological and economic development level of the Poyang Lake area was relatively backward, which leads to low eco-economic efficiency. Like most cities, EWP in the Poyang Lake area is constrained by eco-economic efficiency, suggesting that China still needs to promote the green economic transformation to improve human well-being sustainably [ 12 ]. In addition, the measurement results of this study showed that using a two-stage Super-NSBM model is more accurate and reasonable than using the Super-SBM model, which considers undesired outputs from a single-stage perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Zhu (2013) [ 11 ] introduced the concept of EWP in China and expressed it as the ratio of human development index (HDI) to ecological footprint (EF) that broadens its scope for development. In essence, EWP measures eco-efficiency in terms of enhancing well-being [ 12 ]. Therefore, EWP is an extension of sustainable development, broader than eco-efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Per-capita industrial energy consumption above the scale [46,48,54] Land resource consumption Built-up area per capita [42,46] Water consumption Water consumption per capita [48,55] Undesired output Environmental pollution water pollution Industrial wastewater emissions per capita [27,56] Air pollution Industrial waste gas emissions per capita, per-capita carbon emission [46,56] Land pollution Industrial solid waste generation per capita [24,56] Intermediate ). The China Carbon Accounting Database https://www.ceads.net.cn/ (accessed on 10 November 2022), the water resources bulletins of each district and county, and the China County Construction Statistical Yearbook were also used to acquire data on carbon emissions, water usage, and built-up area.…”
Section: Energy Consumptionmentioning
confidence: 99%
“…Wang, Zhang, and Yao (2021) and Zhou and Zhang (2021) used the super‐SBM model to estimate the EWP of 30 provinces in China. Wang et al (2022) combined subjective and objective well‐being indicators to evaluate EWP in China from 2006 to 2018. Their findings of both studies indicate that the average EWP in China shows a decreasing trend.…”
Section: Literature Reviewmentioning
confidence: 99%